2007
DOI: 10.1253/circj.71.202
|View full text |Cite
|
Sign up to set email alerts
|

Close Relationship Between Sympathetic Activation and Coronary Microvascular Dysfunction During Acute Hyperglycemia in Subjects With Atherosclerotic Risk Factors

Abstract: he Framingham offspring study has demonstrated that post-challenge hyperglycemia is an independent risk factor for cardiovascular disease, 1 and that stress hyperglycemia is one of the determinants of the outcome after myocardial infarction. 2,3 In this context, it is thought that coronary microvascular dysfunction related to stress hyperglycemia might be one of the possible reasons for the poor outcome in patients with acute myocardial infarction with stress hyperglycemia, and also for the improvement of epic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 41 publications
0
32
0
2
Order By: Relevance
“…27- 31 Others have shown that oxidative stress is increased in both type I and type II DM. 32, 33 Hyperglycemia induces oxidative stress through several pathways, 10-13, 34 including enhanced aldose reductase activity, 10 increased advanced glycation end-products, 11 altered protein kinase C activity 12 and mitochondrial overproduction of superoxide. 13 Matsushima et al found that glutathione peroxidase overexpression improved LV diastolic function, accompanied by the attenuation of myocyte hypertrophy, interstitial fibrosis and apoptosis, in mice with STZ-induced DM.…”
Section: Effects Of Fluvastatin On Cardiac Oxidative Stressmentioning
confidence: 99%
“…27- 31 Others have shown that oxidative stress is increased in both type I and type II DM. 32, 33 Hyperglycemia induces oxidative stress through several pathways, 10-13, 34 including enhanced aldose reductase activity, 10 increased advanced glycation end-products, 11 altered protein kinase C activity 12 and mitochondrial overproduction of superoxide. 13 Matsushima et al found that glutathione peroxidase overexpression improved LV diastolic function, accompanied by the attenuation of myocyte hypertrophy, interstitial fibrosis and apoptosis, in mice with STZ-induced DM.…”
Section: Effects Of Fluvastatin On Cardiac Oxidative Stressmentioning
confidence: 99%
“…In addition to an excess of catecholamines, vasospasm and myocarditis may also be related to the onset of TC, although the mechanism of TC is largely unknown. Sympathetic activation is closely related to coronary microvascular dysfunction (18). According to previous reports, left ventricular wall motion abnormalities in TC patients might be associated with coronary microvascular impair- (20).…”
Section: Discussionmentioning
confidence: 94%
“…23 From a vascular biology perspective, the processes of cellular adhesion, monocyte and macrophage attachment, and transmigration of immune cells across the endothelium are crucial steps in early atherogenesis and in the later stages of mature plaque rupture. 24 Inflammatory cells express P2RY2 with multiple effects.…”
Section: Discussionmentioning
confidence: 99%